Did the Dodd–Frank Whistleblower Provision Deter Accounting Fraud? - BERGER, PHILIP G.; LEE, HEEMIN (Journal of Accounting Research, 2022)
ABSTRACT We examine the deterrence effect of the Dodd–Frank whistleblower provision on accounting fraud. To facilitate causal inference, we use state False Claims Acts (FCAs), under which whistleblowing about accounting fraud at a firm invested in by a state's pension fund can result in monetary rewards from that state's government. We divide our sample into firms exposed and not exposed to whistleblowing risk from a state FCA during the 2008–2010 period that preceded the 2011 SEC implementation of the Dodd–Frank whistleblowing provision. We hypothesize that firms already exposed to a state FCA whistleblower law are less affected by the Dodd–Frank whistleblower provision. Using the companies exposed to a state FCA as control firms in our Dodd–Frank tests, the remaining firms constitute the treatment sample. We find that exposure to Dodd–Frank reduces the likelihood of accounting fraud of treatment firms by 12%–22% relative to control firms, but do not find that it affects audit fees.